The impact of public cultural participation on public health efficiency: empirical analysis from Chinese cities - Yang, Lili; Zhang, Ning; Zhang, Zhen (Frontiers in Public Health, 2025)
IntroductionCultural dissemination plays a critical role in shaping public health awareness, helping to cultivate an environment where public health concepts are deeply embedded in the minds of citizens. Understanding the interaction between cultural participation and public health efficiency is crucial, especially in urban settings where the dynamics of market policies and cultural engagement converge.MethodsThis study uses panel data from 154 prefecture-level cities spanning the years 2007 to 2021 to explore the impact of urban residents’ public cultural participation on public health efficiency. A two-way fixed effects model is employed to assess the effects, taking into account the market-policy interaction. The analysis examines the underlying mechanisms, including social capital accumulation, healthy behavior promotion, and service resource coordination.ResultsThe findings indicate that urban residents’ public cultural participation has a significant positive impact on public health efficiency. This effect is primarily driven by increased social capital, improved health behaviors, and better coordination of health service resources. Among the control variables, economic development and population size are found to have a positive influence on health efficiency, whereas industrialization, infrastructure, and urbanization are associated with a significant negative impact.DiscussionThe results highlight the importance of public cultural participation in enhancing health efficiency, suggesting that integrating cultural and health policies could be beneficial for urban public health management. The robustness of the findings is confirmed through a sensitivity analysis, which substitutes alternative measures of public cultural participation. Policy recommendations include promoting “culture-health” integrated governance and optimizing public cultural investment to address health challenges arising from urbanization and industrialization. These measures could help mitigate the adverse health impacts associated with rapid urban development.